PARADIGMA BERPIKIR GURU PENDIDIKAN AGAMA ISLAM DI ERA DISRUPSI - Mirza Mahbub Wijaya (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2019)
Abstract This paper discusses the paradigm of thinking of PAI teachers in the era of disruption. Science as the main capital that must be held by a teacher. In this era of disruption, of course there must be an effort to develop Islamic knowledge located in the hands of PAI teachers. A PAI teacher may be passive. He must always think, research and make various efforts for the development of Islamic science in the midst of globalization. In this way, the task of the chosen strategy is to develop scientific integration that can be taken to develop knowledge that has been less able to dialogue with religion. Paying attention to relations between science without sacrificing autonomy between each discipline and paying attention to the religious dimension of the Indonesian nation. This paper is expected to contribute in developing a theoretical framework and practical strategies in the development of science in Indonesia. Keywords: Paradigm, Islamic Education, Teacher